Occupational Respiratory Symptoms Caused by Chemical Hazard on Hairdresser Workers in Palembang - Andarini, Desheila; Camelia, Anita; Listianti, Ani Nidia (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Respiratory Disease is the leading cause of death in the majority of people and is among the top 10 causes of death in the world. Factors causing respiratory disease are occupational exposure, smoking and lung infections. According to WHO, 65 million people have respiratory illnesses ranging from moderate to severe. Nearly 90% of deaths from respiratory illness occur in low- and middle-income countries. Hairdressers are exposed to many chemicals in the use of many hair products such as shampoos, curling products, hair dyes, and hair sprays. This study aims to obtain risk factor related to occupational respiratory symptoms on hairdresser workers in Palembang. Cross sectional study design was chosen with a sample size of 150 respondents. The result showed that the prevalence of Occupational Respiratory Symptoms was 40%, female hairdresser were 85.3%, 64.7% were less than 35 years old, those with contact duration of eight hours a day was 78.7%, and those with contact frequency of more than three times a day was 86.6%.There were no significant relationship between sex, age and duration of contact with Occupational Respiratory Symptoms. There was a significant relationship between frequency of contact with Occupational Respiratory Symptoms.